Integrating Problem-Based Learning in a Criminal Law Course - Dzul Rachman; Rio Arif Pratama; Ni Wayan Surya Mahayanti; I Putu Indra Kusuma (Script Journal: Journal of Linguistics and English Teaching, 2020)
Background:In this modern era, intelligent and capable human resources to solve issues in the law field are necessary. Project-based learning with technology integration is perhaps one of the solutions to yield such human resources. However, the previous studies did not put much attention on the implementation of technology into project-based learning. This study therefore aims to examine the effect of project-based learning on studentsâ€™ problem-solving abilityMethodology:This study implemented a quantitative approach by administering a quasi-experimental design with the one group design pre-test and post-tests. This study involved 49 students who were taking a criminal law course in a university in Indonesia to obtain the data through administering tests.Findings:The data were then analysed by performing paired sample t-test analysis and showed that t (96) = 67.67, p < 0.001.Conclusion:In conclusion, project-based learning with technology integration can enhance the studentsâ€™ problem-solving ability in a criminal law course. In addition, there are two implications discussed in this article.Â